2021
DOI: 10.1007/s12015-020-10087-6
|View full text |Cite
|
Sign up to set email alerts
|

Results and Prospects of Using Activator of Hematopoietic Stem Cell Differentiation in Complex Therapy for Patients with COVID-19

Abstract: The paper presents the results of a standard and complex treatment method using the peptide drug thymus thymalin in patients with COVID-19. One of the mechanisms of the immunomodulatory effect of thymalin is considered to be the ability of this peptide drug to influence the differentiation of human hematopoietic stem cells (HSCs). It was found that, as a result of standard treatment, patients in the control group showed a decrease in the concentration of the pro-inflammatory cytokine IL-6, C-reactive protein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…They found an accelerated reduction of pro-inflammatory markers, as well as improvement in T cell system indicators. 22 No deaths were reported in any of the groups. 22 However, safety data and time to recovery were not described.…”
Section: Other Clinical Outcomesmentioning
confidence: 89%
See 2 more Smart Citations
“…They found an accelerated reduction of pro-inflammatory markers, as well as improvement in T cell system indicators. 22 No deaths were reported in any of the groups. 22 However, safety data and time to recovery were not described.…”
Section: Other Clinical Outcomesmentioning
confidence: 89%
“…22 No deaths were reported in any of the groups. 22 However, safety data and time to recovery were not described.…”
Section: Other Clinical Outcomesmentioning
confidence: 89%
See 1 more Smart Citation
“…115,123 There are plenty of studies which revealed that in certain cases, various prophylactic measures used to prevent the spread of SARS-CoV-2 and other viruses and bacteria, could have negative effects on the human body, have low efficacy or may even be useless in terms of prevention of diseases. Since the main target for SARS-CoV-2 are people with the weak immunity, 13,[40][41][42] and prolonged mental stress affects both the entire body, [124][125][126]236 and the immune system in particular, [237][238][239][240][241] a new study is needed to answer the question, if medical and non-medical measures used to prevent the spread of SARS-CoV-2 could affect natural immunity. This question is especially relevant for countries which had a dramatic increase in cases and deaths during the third phase of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of thymic reactivation might contribute to a worse prognosis. 97 Despite great importance of immunological dysregulation caused by T-cell deficiency, there were only a few studies with application of thymus derived medicines, 42,61,98 although the immunemodulating and protective effect of thymus extract has already been known for more than two hundred years. 99 On June 16, 2020, Professor Peter Horby said, that dexamethasone "is the only drug so far that has been shown to reduce mortalityand it reduces it significantly".…”
Section: Paradoxes Of Clinical Trialsmentioning
confidence: 99%